Solving reliability analysis problems in the polar space - Ezzati, Ghasem; Mammadov, Musa; Kulkarni, Siddhivinayak (International Journal of Applied Mathematical Research, 2014)
An optimization model that is widely used in engineering problems is Reliability-Based Design Optimization (RBDO). Input data of the RBDO is non-deterministic and constraints are probabilistic. The RBDO aims at minimizing cost ensuring that reliability is at least an accepted level. Reliability analysis is an important step in two-level RBDO approaches. Although many methods have been introduced to apply in reliability analysis loop of the RBDO, there are still many drawbacks in their efficiencies and stabilities. This paper proposes a novel method that converts the constrained reliability analysis problem to an unconstrained minimization problem in order to improve efficiency of the solution. Number of numerical experiments is conducted and then performance of the proposed method is compared with the existing reliability analysis methods.Keywords: Polar space, Reliability analysis, Reliability-based design optimization.